Tracing the source–sink process of fluvio-clastic materials: Magnetic records of surface sediments in the Yangtze River basin - Liu, Xianbin; Chen, Jing; Yue, Wei; Wang, Qing; Zhan, Chao; Zeng, Lin; Song, Jian; Wang, Longsheng; Cui, Buli (Frontiers in Marine Science, 2022)
In this study, we collected surface sediments from the mainstream and major tributaries of the Yangtze River to systematically analyse their magnetic properties, and discuss the implications for tracing source–sink process of fluvio-clastic materials. Our results showed that the surface sediments from tributaries in the upper basin had a significantly higher content of ferromagnetic minerals and coarser grain sizes than that in the mid-lower basin. The magnetic susceptibility (χlf) of surface sediments from the mainstream was 34.16*10-8 m3/kg at Shigu, rapidly rose to 230.56*10-8 m3/kg at Yibin, and then dropped to 68.92*10-8 m3/kg at the river mouth. The χlf of Yalong River sediments in the upper basin was 276.86*10-8m3/kg, considerably higher than that of the sediments from other tributaries, and greatly contribute to the χlf of the sediments in the mainstream, reflecting the dominant constraining role of the Emeishan basalts. The distinctive magnetic properties of the upper core sediments from Jianghan basin and the Yangtze delta closely match those of surficial river sediments of the upper Yangtze basin. This may indicate the addition of clastic materials eroded from the upper basin, resulting from the cut-through of the Three Gorges during the evolution of the Yangtze River that occurred in the late Cenozoic. Investigating the magnetic properties of the surface sediments in the Yangtze River basin can provide insights into the source–sink process of clastic materials and environmental changes.